GAGAL JANTUNG - Mariyono, Harbanu H; Santoso, Anwar (journal of internal medicine; Vol. 9, No. 1 Januari 2008, 2012)
Heart failure were the end stage of all heart disease and the cause of the increasing morbidity and mortality among patient. Almost five percent from all inhospital patient were heart failure. Heart failure has been defined as the failure of the heart to pump blood to systemic. It can be classify into acute, acute decompensated and chronic heart failure. New York Heart Association, Stevenson, Forrester have made classification based on the clinical symptoms. All cardiac problems can ended into heart failure, the pathogenesis was very complex including renin-angiotensin-aldosteron system, neurohormonal, sympatic nerve system, nattriuretic peptide, and others. Twelve leads ECGs, echocardiography, chest x-rays, blood chemistries, catheterisation can help us diagnose patient with heart failure. Management of heart failure consist of management of acute and chronic heart failure, non drugs management, drugs and even an invasive treament.
Keywords: heart failure, definition, classification, diagnosis and treatment